On-line coordination: event interaction and state communication between cooperative agents - Pham, Manh Tung. (2013)
This paper addresses a novel coordination problem for distributed agents in a discrete-event setting. We first introduce and study a predicate coordination problem as the problem of two distributed agents interacting and communicating between themselves to satisfy (the invariance of) a global predicate specifying an inter-agent constraint. We then develop an optimal coordination policy by which the agents can coordinate to satisfy the predicate constraint. To implement the optimal policy, we develop two on-line coordination strategies including one that can achieve significant savings in communication bandwidth, as demonstrated by simulations. An extension to on-line coordination among multiple agents satisfying multiple constraints is then developed and discussed.